Publication strategies under the Publish or Perish Paradigm – using Kolb’s ELT to understand PhD students’ needs - Nordahl Wien, Charlotte; Dorch, Bertil F.; Bredahl, Lone; Brandt Eriksen, Mette (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
Having a viable publication strategy at an early stage of the career can nowadays make a researcher. Not having one appears to break them. We as librarians are in a unique position to guide them in their endeavours to create a viable publication strategy. In this paper we use Kolb’s Experiential Learning Theory as our theoretical framework for understanding learning processes related to the development of a publication strategy. We compare a set of publication strategies developed by newly enrolled PhD students 4 to 5 years ago to articles retrieved from PubMed and Scopus using the PhD students’ ORCID as identifier. We subdivide the publication strategies into three categories (fulfilled, partially fulfilled, abandoned). We find evidence that the more realistic the publication plan is, the more likely it is to be followed. This indicates that it is of importance that PhD schools support students’ efforts in developing their publication strategy at an early stage of their career.